1996
DOI: 10.2307/2136191
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Compliance Among Oral Contraceptive Users

Abstract: Irregular use of the pill compromises the effectiveness of this highly reliable method. The consistency of pill-taking has traditionally been estimated through women's own reports of their patterns of pill use. In this study, self-reported data on pill-taking were compared with data from an electronic device measuring compliance among 103 women attending university health services and publicly funded family planning clinics. In three months of pill use, the electronic and self-reported data agreed on the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(117 citation statements)
references
References 20 publications
2
110
1
4
Order By: Relevance
“…Previous studies show that 50% of young women report imperfect pill use during a pill cycle [11,28]. Approximately 25% of OCP users miss two or more pills during a pill cycle, placing them at increased pregnancy risk [12,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies show that 50% of young women report imperfect pill use during a pill cycle [11,28]. Approximately 25% of OCP users miss two or more pills during a pill cycle, placing them at increased pregnancy risk [12,29].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many participants who identified themselves as OCP users were in method transition, associated with less consistent pill-taking and condom use. Thus, earlier research with less-well-specified identification of OCP method use may overestimate the degree of protection among adolescent OCP users [11,12,17,28,29]. However, it does appear that the stable OCP method use group is slightly more likely to cover coital events with condoms, although the extent to which condoms were utilized correctly was not specifically investigated.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Women may use more than one type of contraceptive, Overall, our research found that the majority of women over 30 years of age used contraception at the time of conception in relation to a termination of pregnancy at the health service in South Australia. However, previous research in the USA found overreporting of compliance with contraceptive regimes by some women (Potter 1996).…”
Section: Discussionmentioning
confidence: 86%